PROSES PEMEKARAN KABUPATEN BANDUNG BARAT SEBAGAI DAERAH OTONOM - Fitri Nur Endah, Annisa; ,, Turtiantoro; ., Supratiwi (Journal of Politic and Government Studies, 2013)
AbstractRegional expansion became a phenomenon after the reform era in Indonesia. The manifestation of democracy in the autonomous region has given rise to so many new autonomous region. The growth of new autonomous region in Indonesia became a controversy, due to the increased quantity of autonomous regions in Indonesia are not accompanied by an increase in the quality of its performance. West Bandung Regency is an autonomous region that was inaugurated in 2007, this area was chosen as the locus of the study. This research used qualitative method with descriptive qualitative type that will present the data in accordance with the findings and facts on the ground. This research has a focus problem that explore the reasons and considerations of regional expansion and examines the expansion process of West Bandung Regency. The findings of the research in the field shows that the reasons and considerations of regional expansion motivated by Bandung Regency’s geography that has a broad area and motivated by aspirations of the people who gathered on Committee Of West Bandung Region Formation. The process of expansion carried out in accordance with current regulations that the Government Regulation No. 129 of 2000 on the establishment of requirements and criteria for expansion, deletion and merging areas. The expansion which have been implemented should be a contributing factor in the successful development of the area as shorten the span of control of government to accelerate the development effectively. Strong aspiration of the people should be accommodated into the social capital to implement the accelerated development of the region.Keywords: regional expansion, autonomous region